Association of salivary alpha-amylase with anxiety and stress in nursing professionals - Sergio Valverde Marques dos Santos; Luiz Almeida da Silva; Fábio de Souza Terra; Adriele Vieira de Souza; Foued Salmen Espindola; Maria Helena Palucci Marziale; Renata Roland Teixeira; Maria Lucia do Carmo Cruz Robazzi
Objective: to assess if changes in salivary alpha-amylase activity are associated with anxiety and stress among hospital nursing professionals and whether anxiety and stress are associated with sociodemographic, epidemiological, and occupational factors. Method: cross-sectional, quantitative study, carried out with 210 nursing professionals from a hospital. For data collection, we used a questionnaire to characterize workers, Beck's Anxiety Inventory, Lipp's Stress Symptoms Inventory for Adults and samples and saliva samples collected in work shifts. The data were analyzed descriptively and inferentially using the software Statistical Package for the Social Science and GraphPad Prism. Results: most professionals experienced stress and anxiety. The variables age group, number of children, use of medication and workload were associated with anxiety; age group, smoking and medication use were associated with stress. An increase in the salivary alpha-amylase activity was observed in the middle of the work shift. Professionals who had stress and anxiety had significant changes in alpha-amylase in the night shift. Conclusion: changes in salivary alpha-amylase were associated with anxiety and stress among nursing professionals, indicating that this enzyme can be a possible biomarker of anxiety and stress in workers.